Between Policy and Practice: A Longitudinal Reflection on the Implementation of the ENEC in Portugal (2017–2025) (Revista Lusófona de Educação, 2025)
This article analyzes the implementation of the National Strategy for Citizenship Education (ENEC, 2017) and the subject Citizenship and Development (CD) in Portugal between 2017 and 2025. Drawing on a qualitative and longitudinal approach, which combined 20 focus group discussions conducted in three phases (2020, 2023, and 2025) and the analysis of the External Evaluation of Curricular Autonomy and Flexibility, it seeks to understand teachers’ and students’ perceptions as well as to identify organizational, pedagogical, and assessment practices over time. Findings reveal that although widely recognized as relevant, CD is often perceived as the “poor relative” of the curriculum, constrained by teacher resistance, weak institutional integration, and the predominance of transmissive and classificatory practices. The article concludes that consolidating CD requires mobilizing pedagogical leadership, specific training, stronger curricular articulation, and assessment criteria aligned with a formative logic, highlighting the persistent gap between policy and the challenges of consolidating a democratic and participatory school culture.Keywords: Citizenship Education; Educational Policy; Teachers and Students’ perceptions; Democratic school culture